Breaking Soybean Yield Barriers: A Cropping Systems Approach - G. R. Balboa; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Two soybean research trials were conducted at Scandia, KS, in dryland and irrigated environments. The objective of this trial was to study the contribution of different farming systems to developing efficient and high-yielding soybean production systems. Each experiment had five treatments: farmer practices (FP), comprehensive fertilization (CF), production intensity (PI), ecological intensification (CF + PI), and advanced plus (AD). Under dryland, FP and CF treatments yielded 34 bu/a, differing in 27 bu/a compared with PI, EI, and AD scenarios. Under irrigation, FP and CF presented comparable yield levels, differing by close to 36 bu/a compared with crop intensification treatments (CF + PI; AD).
Keywords: soybean; yield barriers; cropping systems